The Prevalence and Correlates of Fissured Tongue Among Outpatients in Andkhoy City, Afghanistan: A Cross-Sectional Study - Hamrah MH; Baghalian A; Ghadimi S; Mokhtari S; Kargar M; Khosrozadeh M; Dahi T; Charkazi A; Hamrah MS; Hamrah MH (Dove Medical Press, 2021)
Mohammad Hassan Hamrah,1,2 Ali Baghalian,1 Sara Ghadimi,1 Saeedeh Mokhtari,1 Mojgan Kargar,3 Maryam Khosrozadeh,1 Toba Dahi,4 Abdurrahman Charkazi,5 Mohammad Shoaib Hamrah,6 Mohammad Hussain Hamrah2 1Department of Paediatric Dentistry, School of Dentistry, Tehran University of Medical Sciences, Tehran, Iran; 2Curative Clinic, Andkoy, Faryab, Afghanistan; 3Department of Paediatric Dentistry, School of Dentistry, Shahid Sadoughi University of Medical Sciences, Yazd, Iran; 4Abant Izzet Baysal University Faculty of Dentistry, Bolu, Turkey; 5Health Education and Promotion, Environmental Health Research Center, Faculty of Health, Golestan University of Medical Sciences, Gorgan, Iran; 6Shaheed Ostad Esmail"Aslam" Aimaq Hospital, Anadkhoy, Faryab Province, AfghanistanCorrespondence: Mohammad Hussain HamrahCurative Clinic Andkhoy, Amir Timor Street, Shari now, Andkhoy, AfghanistanEmail hkmu1991@gmail.comBackground: Fissured tongue is a common manifestation of the tongue, marked by the presence of multiple prominent grooves or fissures on the dorsal surface of the tongue. However, there is a lack of studies focusing on the prevalence and factors associated with fissured tongue among patients attending an outpatient clinic in Afghanistan.Aim: The purpose of the current study was to determine the prevalence and factors associated with fissured tongue and its effects on the general health of adult outpatients in Afghanistan.Patients and Methods: The cross-sectional survey was conducted among outpatient populations in Andkhoy City, Afghanistan, between September 2019 and December 2019. A convenience technique was applied by including 1182 patient aged 18- 80 years. Socio-economic status, smoking, nass use (smokeless tobacco use) and medical data were collected using face-to-face interviews. We used logistic regression analysis to identify factors associated with fissured tongue. A convenience technique was applied by including patient aged 18- 80 years.Results: The studied population consisted of 1182 participants, of whom 573 (48.5%) were males and 609 (51.5%) females. The prevalence of fissured tongue was 27.2% (95% CI: 24.7- 29.9%) with males having significantly higher prevalence than females (47.5%, 95% CI: 43.3- 51.6% versus 8.2%, 95% CI: 6.2- 10.7%, p< 0.001). Male participants (OR=7.1, 95% CI: 4.8- 10.3), diabetes mellitus (OR=1.6, 95% CI: 1.1- 2.3) and smokeless tobacco use (OR=12.0, 95% CI: 8.1- 17.6) were the only variables independently associated with fissured tongue.Conclusion: This study suggested that there was a high rate of fissured tongue among an outpatient clinic in Andkhoy, Afghanistan. Male gender, diabetes mellitus, and nass consumption were associated with fissured tongue. Therefore, these factors might usefully be targeted in local health promotion, prevention and early intervention programs.Keywords: fissured tongue, prevalence, risk factors, Andkhoy, Afghanistan